The Complete Mitochondrial Genome of Glischropus bucephalus (Vespertilionidae; Chiroptera) Provides New Evidence for Pipistrellus Paraphyly - Svetlana S. Zhukova; Anna S. Speranskaya; Alexandra A. Lisenkova; Sergei V. Kruskop (Diversity, 2023)
The Indochinese thick-thumbed bat, Glischropus bucephalus, was described in 2011, but its molecular genetics (and the genetics of the whole genus Glischropus) are still poorly studied. We defined and annotated the complete mitogenome of Glischropus bucephalus (Chiroptera: Vespertilionidae) from Vietnam. The complete mitogenome is 17,023 bp in total length, which includes 13 complete protein-coding genes, 22 tRNA genes, 2 rRNA, and one non-coding region (the origin of replication). The nucleotide composition is 33.2% A, 29.7% T, 13.6% G, and 23.5% C. The mitochondrial protein-coding genes use the standard start codon (ATN), one complete stop codon (TAA), and two incomplete stop codons (TA- and T-). The phylogenetic analysis confirmed that the genus Glischropus belongs to the Pipistrellini tribe and revealed that Glischropus bucephalus is clustered with the “eastern” clade of Pipistrellus, supporting the paraphyletic nature of the latter genus.